Bacterial Biotransformation and Anticancer Activities of Betulin against A549, HepG2 and 5RP7 Cancer Cell Lines - Kıran, İsmail and Çiftçi, Gülşen A. and Eklioğlu, Özlem A. and Akkaya, Şaziye G.K. (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: A pentacyclic lupenane-type natural triterpenoid, betulin, has attracted attention in the field of medicinal chemistry since it exhibited a variety of biological activities, including anticancer activity. Objective: The aim of this present work was to obtain derivatives of betulin through bacterial biotransformation and investigate its anticancer activity against A549, HepG2 and 5RP7 cancer cell lines. Methods: Bacterial biotransformation studies were continued in an MBH broth medium for 7 days at 35oC. Anticancer activities of betulin against A549, HepG2 and 5RP7 cell lines were carried out using XTT assay, and their selectivity was determined using a healthy cell line of NIH/3T3. Cell proliferation ELISA, BRDU (colorimetric) assay was used for measuring proliferation in replicative cells in which DNA synthesis occurs. Flow cytometric analysis was used for measuring apoptotic cell percentages, caspase 3 activation and mitochondrial membrane potential. Results: Bacterial biotransformation studies with 7 bacteria of Staphylococcus aureus ATCC 6538, Proteus vulgaris NRRL B-123, Bacillus subtilis NRRL B-4378, Streptomyces griseolus NRRL B-1062, Escherichia coli ATCC 8739, Staphylococcus aureus ATCC 43300 and Bacillus velezensis NRRL B-14580 produced no metabolite. In in vitro anticancer activity studies, betulin was found to exert anticancer activity against A549, HepG2 and 5RP7 cell lines with IC50 values of 207.7, 125.0 and 28.3 μg/mL, whereas SI values were found to be 30, 50 and 223, respectively. Early and late apoptotic percentages of betulin were found as 9.6, 12.1 and 85.4% on A549, HepG2 and 5RP7, respectively, while caspase 3 positive cell percentages were 2.3, 28.7 and 13.3% for IC50 concentrations. In addition, betulin caused G1 cell cycle arrest (49.5%) on 5RP7 cell line. Conclusion: The results have been shown that betulin activities against A549 and HepG2 cell lines were nonselective and limited its cytotoxic activity against healthy cells, but it is possible to say that it exerted selective activity against 5RP7 cell (28.33±1.53 μg/mL). Betulin effects on apoptosis were found to be dosedependent, while its effect on caspase 3 activation, mitochondrial membrane potential, and cell cycle arrest on G0/G1 phase was not dependent on doses. Therefore, betulin could be a good candidate for the treatment of H-ras active cancer types.
Keywords: betulin